Sosialisasi Literasi Keuangan Syariah bagi Pelaku UMKM melalui Pendekatan Participatory Action Research di Desa Batu Gajah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aimed to improve Islamic financial literacy among Micro, Small, and Medium Enterprises (MSMEs) in Batu Gajah Village, Rupit District, North Musi Rawas Regency. The program was motivated by the limited understanding of MSME actors regarding financial management based on Islamic principles and the continued practice of interest-based financing. The program employed a Participatory Action Research (PAR) approach involving 23 MSME participants through initial mapping, socialization, practical assistance, and handbook distribution. The results demonstrated improved participant understanding of the prohibition of riba, gharar, and maysir, as well as the importance of maintaining simple and systematic business financial records. Collaboration with Bank Syariah Indonesia supported the delivery of relevant and credible educational materials. The handbook provided during the program served as an effective educational medium for continuous learning. The program demonstrated that a participatory approach can improve MSME actors’ understanding and awareness of Islamic financial principles. The activity is expected to encourage more responsible financial behavior and expand access to Islamic financial services at the community level. Furthermore, sustained mentoring and periodic evaluation are recommended to ensure that the knowledge gained is consistently applied in daily business financial management.